In-vivo X-ray dark-field computed tomography for the detection of radiation-induced lung damage in mice. (October 2021) - Burkhardt, Rico; Gora, Thomas; Fingerle, Alexander A.; Sauter, Andreas P.; Meurer, Felix; Gassert, Florian T.; Dobiasch, Sophie; Schilling, Daniela; Feuchtinger, Annette; Walch, Axel K.; Multhoff, Gabriele; Herzen, Julia; et al.
Highlights: Radiation-induced lung damage was observed using X-ray dark-field tomography. In this pre-clinical study, mouse lungs were irradiated and subsequently imaged. We report increased sensitivity of X-ray dark-field tomography over absorption-based tomography. Abstract: Background and Purpose: Radiotherapy of thoracic tumours can lead to side effects in the lung, which may benefit from early diagnosis. We investigated the potential of X-ray dark-field computed tomography by a proof-of-principle murine study in a clinically relevant radiotherapeutic setting aiming at the detection of radiation-induced lung damage. Material and Methods: Six mice were irradiated with 20 Gy to the entire right lung. Together with five unirradiated control mice, they were imaged using computed tomography with absorption and dark-field contrast before and 16 weeks post irradiation. Mean pixel values for the right and left lung were calculated for both contrasts, and the right-to-left-ratio R of these means was compared. Radiologists also assessed the tomograms acquired 16 weeks post irradiation. Sensitivity, specificity, inter- and intra-reader accuracy were evaluated. Results: In absorption contrast the group-average of R showed no increase in the control group and increased by 7% (p = 0.005) in the irradiated group. In dark-field contrast, it increased by 2% in the control group and by 14% (p = 0.005) in the irradiated group. Specificity was 100% for both contrasts but sensitivity was almost four times higher using dark-field tomography. Two cases were missed by absorption tomography but were detected by dark-field tomography. Conclusions: The applicability of X-ray dark-field computed tomography for the detection of radiation-induced lung damage was demonstrated in a pre-clinical mouse model. The presented results illustrate the differences between dark-field and absorption contrast and show that dark-field tomography could be advantageous in future clinical settings.